Halal certification awareness among food and beverages entrepreneurs in Majalengka West Java Indonesia - Septi, Iti (International Institute for Halal Research and Training, International Islamic University Malaysia, 2022)
This research explores halal certification awareness among entrepreneurs who are directly involved in the practice and implementation of the production process and the application of halal certification. In this research, 30 entrepreneurs and 3 experts were selected to participate. The instruments used to generate data were semi-structured interviews and observation. The experts were sought to identify the reliability of the generated themes and sub-themes of the research. Member checks and a pilot study were also conducted to ensure the data’s credibility. This study found several internal and external factors influencing the level of the entrepreneurs’ awareness. The internal factors include socio-demographic factors, personal factors, and family factors, which are believed to affect the attitude of entrepreneurs. Additionally, external factors, such as the social effects influenced by a community, can also impact their awareness. Moreover, awareness is also related to the entrepreneurs’ behaviour. It can be seen from their attention towards halal certification, motivation in producing halal products, and proactiveness in producing halal products, and applying for the halal certification. This research’s halal awareness concerns halal products and certification among Muslim business owners in Majalengka. This study aims to raise halal certification awareness among food and beverage entrepreneurs by enhancing their personalities, identifying the factors of halal certification awareness that influence their intention to apply for halal certification, and analysing the practice of halal certification implemented in products supported by the Halal Assurance System (HAS). This research used a small sample size and a qualitative approach. The qualitative method was used to stimulate responses by interview questions. Atlas.ti software were also used to analyse data, and thematic analysis was used to determine the factors affecting the entrepreneur awareness towards the importance of halal certification. By employing thematic analysis, several reasons were discovered as factors that influence the importance of halal certification among entrepreneurs. From this discovery, an Islamic framework was suggested as a model for halalpreneurs for entrepreneurs in Majalengka. Improvement to the Islamic framework to become a halalpreneurs is thought to positively affect the successful implementation of halal awareness in halal certification. This research aims to benefit entrepreneurs, the community, and the government, particularly in the Majalengka district and throughout Indonesia.